«The hundred-thousandth part of what exists», or, representing Maupassant’s Horla in visual media - Reis, Amândio (2017)
Since Lettre d’un fou (1885), a short story written by Guy de Maupassant, the still-growing Horla mythography has spawned two re-writings by the author himself (the short story Le Horla, in 1886, and a longer novella with the same title in the following year), and has been the inspiration for: 1) a number of literary works, such as Ambrose Bierce’s The Damned Thing, in 1893; H.P. Lovecraft’s The Call of Cthulhu, in 1928; and Manly Wade Wellman’s The Theatre Upstairs, in 1936, among others; 2) at least two surviving radio dramas (episode 31 of the second season of Inner Sanctum Mystery, broadcast on August 1, 1943; and episode 3 of the 1947 season of the Mystery in the Air series, narrated by Peter Lorre); 3) a loose film adaptation, Diary of a Madman, directed by Reginald Le Borg and brought to the big screen in 1963; and several short films (including Jean-Daniel Pollet’s Le Horla, premiered in 1966); 4) a progressive rock album by Canadian band The Box, released in 2009 and adequately entitled D’Après Le Horla De Maupassant; 5) and, more recently, a graphic novel by French author and illustrator Guillaume Sorel, published by Rue de Sèvres in 2014.